The Involvement of Angiotensin Type 1 and Type 2 Receptors in Estrogen-Induced Cell Proliferation and Vascular Endothelial Growth Factor Expression in the Rat Anterior Pituitary - Hanna Lawnicka; Dorota Ptasinska-Wnuk; Slawomir Mucha; Jolanta Kunert-Radek; Marek Pawlikowski; Henryk Stepien (The Scientific World Journal)
The aim of our study was to examine the involvement of renin-angiotensin system (RAS) in estrogen-induced lactotropes proliferation and vascular endothelial growth factor (VEGF) expression in rat pituitary. The study was performed on Fisher 344 rats underwent 8-day treatment with diethylstilboestrol (DES). The proliferation index (PCNA) and VEGF expression in pituitary sections were estimated using immunohistochemical methods. Treatment with DES increased the number of PCNA-positive cells, VEGF-positive cells, and VEGF-positive blood vessels in pituitary. Stimulatory effect of estrogen on cell proliferation and VEGF expression in blood vessels was attenuated by losartan, PD123319, and captopril. VEGF immunoreactivity in pituitary cells of DES-treated rats was decreased by AT1 antagonist and not changed by AT2 blocker and ACE inhibitor. Our findings suggest the involvement of RAS in DES-induced cell proliferation and VEGF expression in pituitary. Both the AT1 and AT2 receptors appear to mediate the estrogen-dependent mitogenic and proangiogenic effects in rat pituitary.